Modeling respiration rate of fresh-cut sweet potato (Anggun) stored in different packaging films - Azhar Shapawi, Zahrah Izati; Ariffin, Siti Hajar; Shamsudin, Rosnah; Mohamed Amin Tawakkal, Intan Syafinaz; Gkatzionis, Konstantinos (Elsevier, 2021)
This study is to model the respiration rate and to evaluate the quality attributes of fresh-cut Anggun stored at different storage and packaging treatments. Fresh-cut Anggun was packed in three different packaging films; nylon (OTR: 55 cc/m2/day, WTR: 334 g/m2/day), polyethylene terephthalate, PET (OTR: 90 cc/m2/day, WTR: 35 g/m2/day), and low-density polyethylene, LDPE (OTR: 8000 cc/m2/day, WTR: 200 g/m2/day) and stored at 5℃ and 30℃. Regardless of the film type used in this study, fresh-cut Anggun was found to have shelf life up to 14 days when stored at 5℃ and up to 8 days when stored at 30℃. At both temperatures, samples stored in nylon showed the best performance compared to those stored in PET and LDPE by retaining the purplish color longer, having better texture and lowest respiration rate. Uncompetitive Michaelis-Menten model was proven to show good fit in modeling the respiration rate of fresh-cut Anggun.